An evaluation of vocational high schools in Indonesia: A comparison between four-year and three-year programs - Soenarto Soenarto; Muhammad Mustaghfirin Amin; Kumaidi Kumaidi (REID (Research and Evaluation in Education), 2017)
The research aimed to gain insights into the quality of four-year program vocational high school (VHS) in Indonesia compared to four-year program VHS. This research was conducted based on the school graduate standard, business sector and industrial sector (or Dunia Usaha dan Dunia Industri (DUDI)) – or the performance of the graduates and alumni (the graduates’ satisfaction). The research was conducted using Discrepancy Evaluation Model using 16 VHSs (eight four-year program VHSs and eight three-year program VHSs). The result shows that from the standpoint of the school, the graduates of the four-year program VHS are higher in quality than those of the three-year program VHS. The four-year program VHS graduates are more qualified in seven aspects: teamwork, discipline, tenacity, theoretical knowledge, confidence, creativity, and leadership. Meanwhile, using DUDI standpoint, the four-year program VHS graduates are also higher in quality than the three-year program VHS graduates. In addition, the four-year program VHS graduates are better in the quality of their discipline, tenacity, theoretical knowledge, practical skills, confidence, carefulness, creativity, and leadership. The four-year program VHS graduates have a higher level of satisfaction in terms of income than the three-year program VHS graduates. The higher quality of the four-year program VHS graduates has resulted from longer duration of the internship program (PKL) that provides them with reliable experience and skills concerning work-related problem-solving activities.